Factors Supporting the Quality of One Stop Service at Religious Court Class 1B : Faktor Pendukung Kualitas Pelayanan Terpadu Satu Pintu di Pengadilan Agama Kelas 1B - Lailia, Yolla Nur; Choiriyah, Ilmi Usrotin (Indonesian Journal of Public Policy Review, 2023)
The purpose of this study was to determine and analyze the Supporting Factors of the Quality of One Stop Services Study at the Bangil Religious Court Class 1B, Pasuruan Regency. Qualitative descriptive research methods and data collection techniques through interviews, observation and documentation. Determination of informants is done by purposive sampling method. Data analysis techniques through data collection, data reduction, data presentation, drawing conclusions. The results of this study indicate that the Supporting Factors for the Quality of One-Stop Integrated Service Study at the Bangil Religious Court Class 1B, Pasuruan Regency, have continuous employee direction to improve the competence of employees, one of which can be obtained through coaching. adequate facilities and infrastructure, and employee discipline in implementing SOP (Standard Operating Procedures) services, because discipline is education or training for employees who have focused on developing a good attitude towards work.